(3GdeUGOQs - (3GdMSjfj Hf CMeO Hf GdMSjfj GdRhRfj, CHh YHO Gddg,J (B486 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi ShGHZ BdGFI GdeJSGHbI CahGLkG bGd GdbGVi GdEeGe gPg eUGOQ JQLeJgG hfbMJgG hLQOJgG Yf ThGgO GdMOjK hGdCeKGd hGdCTYGQ s
(3BNQgG (B:s
(3ef HGH aYd jaYd HcSQ GdYjf H (B: (3GdMSHGf hGdeMSHI GdeYJd GddjGFi S (B: (3GdjCS jjCS dZI , hGddg CYde HGdUhGH , Je GdcJGH s
(3GdeNWhW HGdYQHjI hGdaGQSjgs
(3HgG WjGQGJs
(3fSNI KGdKIs
(3hQOJ CjVkG JMJ Qbe (B168 (3Yde dZI (B" (3GdUMjaI GdYPQGA(B"s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GddZIs